2006
DOI: 10.1128/jb.188.5.1920-1928.2006
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the LlaKR2I Methylase in Expression of the AbiR Bacteriophage Defense System in Lactococcus lactis subsp. lactis biovar diacetylactis KR2

Abstract: The native lactococcal plasmid, pKR223, from Lactococcus lactis subsp. lactis biovar diacetylactis KR2 encodes two distinct bacteriophage-resistant mechanisms, the LlaKR2I restriction and modification (R/M) system and the abortive infection (Abi) mechanism, AbiR, that impedes bacteriophage DNA replication. This study completed the characterization of AbiR, revealing that it is the first Abi system to be encoded by three genes, abiRa, abiRb, and abiRc, arranged in an operon and that it requires the methylase ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Lactococcus lactis has been a productive model to discover abortive mechanisms as 23 different lactococcal Abi systems have been reported (Chopin et al ., ; Durmaz and Klaenhammer, ; Holubova and Josephsen, ; Haaber et al ., ). Usually, the resistance phenotype is mediated by a single host gene, except for AbiE, AbiG, AbiL, AbiT and AbiU, which are encoded by two genes, AbiR, encoded by possibly four genes and AbiS, composed of a specific DNA structure (Dai et al ., ; Josephsen and Neve, ; Chopin et al ., ; Yang et al ., ). Most of these genes have been found on plasmids (Chopin et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Lactococcus lactis has been a productive model to discover abortive mechanisms as 23 different lactococcal Abi systems have been reported (Chopin et al ., ; Durmaz and Klaenhammer, ; Holubova and Josephsen, ; Haaber et al ., ). Usually, the resistance phenotype is mediated by a single host gene, except for AbiE, AbiG, AbiL, AbiT and AbiU, which are encoded by two genes, AbiR, encoded by possibly four genes and AbiS, composed of a specific DNA structure (Dai et al ., ; Josephsen and Neve, ; Chopin et al ., ; Yang et al ., ). Most of these genes have been found on plasmids (Chopin et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…A slight increase of specific transcript after phage infection was demonstrated only for abiP gene [ 26 ]. However, some experimental data suggests post-transcriptional regulation of expression and/or function of lactococcal abi s. AbiR requires an associated methylase to protect the host from its own action [ 21 ]. Cloning of intact abiG was shown to be lethal for heterologous E. coli cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The observed difference in efficiencies can also be caused by the fact that MG1614[pCH1, pAW122] contains two similar Abi systems in contrary to MG1614[pCH1, pJW566], which contains AbiS in combination with an R/M system. Many other groups have shown that the addition of R/M system with an Abi system in the same strain can significantly improved the phage resistance phenotype in L. lactis (Yang et al . 2006; Durmaz and Klaenhammer 2007).…”
Section: Discussionmentioning
confidence: 99%
“…2006). Other phenotypic characteristics can include reduction in plaque size due to decreased burst size of the bacteriophage, and may or may not have a reduction in the efficiency of plaquing (EOP) of the bacteriophage (Yang et al . 2006).…”
Section: Introductionmentioning
confidence: 99%